Role of endoscopy in gastroesophageal reflux disease - Tarun Rai (Journal of Digestive Endoscopy, 2015)
Gastroesophageal reflux disease is a condition due to reflux of stomach content in the esophagus causing trouble symptoms or complications or both. GERD is a clinical diagnosis and typically presents with a heartburn and/or regurgitation and a positive response to antacid secretory medications. GERD is the leading outpatient diagnosis among all gastrointestinal disorders in the United States. Approximately 40% of population report occasional symptoms of GERD whereas 10-20% of patients will have symptoms at least once in a week. Recent guidelines from gastrointestinal societies such as American College of Gastroenterology, American Society for Gastrointestinal Endoscopy and American College of Physicians have laid out specific indications regarding role of esophagogastroduodenoscopy in GERD. Despite these recommendations, studies have revealed that one-fifth to two-fifth EGDs may not be clinically indicated, especially where open access endoscopy referral system is used. Traditionally, GERD has been thought to be a disease of the western world. Prevalence rates had been estimated to be lower in Asia when compared to that of the Western Countries. Few recent epidemiological studies in India showed the prevalence of reflux disease in India to be between 8-24%, which is comparable to the western world. The use of EGDs becomes more critical for developing countries such as India where prevalence of GERD and BE is comparable to the western countries but have limited resources. In addition to direct cost for an EGD, it burdens economy with indirect costs such as time off from the work, transportation and any procedural complications. Risk stratifying patients with GERD may therefore prevent unnecessary procedures, harms and costs. The aim of this paper is to review the existing evidence on the role of endoscopy in GERD.